Tumor Necrosis Factor Alpha Knockout Promotes Adipose Fatty Acid Oxidation and Attenuates Insulin Resistance and Hepatic Steatosis in High Fat Diet-Fed Mice. (29th May 2020) - Yu, Seok-Yeong; Li, Jinchao; Liu, Zhenhua; Kim, Young-Cheul
Abstract: Objectives: Substantial evidence indicates that adipose tissue (AT) dysfunction and lipid spillover in obesity promote insulin resistance and non-alcoholic fatty liver disease. Tumor necrosis factor alpha (TNFα) is one of the pro-inflammatory cytokines overexpressed in obesity and its knockout (KO) attenuates diet-induced adiposity, lipid deposition in the liver and insulin resistance. However, the potential roles played by TNFα in fatty acid metabolism in AT have been incompletely understood. The objective of this study was to investigate the role of TNFα in obesity-induced insulin resistance with the goal of providing a potential target for therapeutics. Methods: Three groups of wild type (WT) or TNFα KO male mice on the same B6 genetic background were fed designated diets for 16 weeks; WT fed a low-fat diet (LFD-WT), WT fed a high-fat diet (HFD-WT), and TNFα KO fed a HFD (HFD-TNFα KO). Blood concentrations of glucose and insulin and hepatic triacylglycerol (TG) levels were measured. The expression of genes involved in fatty acid and TG synthesis and fatty acid oxidation (FAO) was measured in epididymal white AT (eWAT). Results: Compared to the LFD-fed mice, HFD-WT group had a significantly higher levels of blood glucose and insulin, and hepatic TG ( P < 0.05). TNFα KO mice significantly improved HFD-induced hyperglycemia, hyperinsulinemia and hepatic TG accumulation ( P < 0.05). In eWAT, TNFα ablation did not affect the expression of de novo fatty-acid synthesis-related genes, but significantly increased the expression of TG synthesis-related genes (p < 0.05). Moreover, TNFα KO presented a significantly increased expression of the FAO-related gene, CPT1, with a concomitant increase in the expression of glucose transporter 4 (GLUT4) and oxidative phosphorylation-related genes (CS and mt-CO1) ( P < 0.05). Further evidence of the inhibition of fatty acid metabolism by TNFα includes a significant suppression of CPT1 as well as TG synthesis-related genes ( P < 0.05) in 3T3-L1 adipocytes treated with TNFα. Conclusions: These data indicate that antagonizing TNFα may mitigate diet-induced insulin resistance and hepatic steatosis by promoting FAO in obese AT. Funding Sources: N/A.